Compared with Genetic Algorithm Fast – MCD – Nested Extension and Neural Network Multilayer Back propagation - منفي, صباح; عبد الحميد, فاطمة (Journal of Economics and Administrative Sciences, 2016)
The study using Nonparametric methods for roubust to estimate a location and scatter it is depending  minimum covariance determinant of multivariate regression model , due to the presence of outliear values and increase the sample size and presence of more than after the model regression multivariate therefore be difficult to find a median location .        It has been the use of genetic algorithm Fast – MCD – Nested Extension and compared with neural Network Back Propagation of multilayer in terms of accuracy of the results and speed in finding median location ,while the best sample to be determined by relying on less distance (Mahalanobis distance)has the study showed the efficiency of neural network in application which represented less distance and smaller determinant matrix of  variance covariance compared with sample of Fast – MCD – Nested Extension .                                                                                                 As for practical side has been 9 kinds of chemical and physical indicators for water pollution, the research covered all the provinces of Iraq except Kardistan region and ten month of the year in 2013 and sample size of 898 .